Experimental and practical investigation of the sealing efficiency of cement grouting in tortuous fractures with flowing water. (February 2021) - Du, Xueming; Fang, Hongyuan; Wang, Shanyong; Xue, Binghan; Wang, Fuming
Highlights: Water plays a role in diffusion mechanism of cement slurry in fracture. There is a strong correlation between the sealing efficiency and fracture tortuosity. There is a consistent rule of between diffusion pressure and sealing efficiency. Abstract: The diffusion of cement slurry in a fracture with flowing water is an important factor ensuring the grouting effect and a key factor influencing the environment, including natural and social traffic. To better understand the influence of the characteristic fracture parameters and the water flow rate on the cement slurry diffusion law, first, diffusion testing of a cement slurry in a simulated tortuous fracture with flowing water is carried out. Then, the results obtained from these tests are applied to an engineering site. The results of the experimental and engineering tests support the following conclusions. 1) At a low water flow rate, the sealing efficiency of test points near the grouting source increases rapidly with time, while the sealing efficiency of test points far from the grouting source exhibits little change with time. 2) Near the grouting source, the sealing efficiency corresponding to a high fractal dimension of fracture tortuosity is higher than that corresponding to a low fractal dimension of fracture tortuosity; far from the grouting source, this pattern is reversed. 3) When the inflection point of the grouting pressure is reached at a test point, the sealing efficiency of the fracture at this test point is the greatest.